Thematic and Integrated Approach to English Material Development - I Made Markus (TEFLIN, 1997)
Abstract: This article discusses and gives an example of how English material development should be done using the thematic approach as suggested by the 1994 English curriculum of SMU (high school) and using the integrated approach in which various language exercises (pronunciation, vocabulary, structure and the four skills) are integrated naturally in line with what happens in real life communication. The example given is to develop a unit of English material with the theme of Student Exchange and the sub-theme of Looking for an Accommodation so the students will be able to use English in their effort to find a good accommodation when they have the chance to join a Student Exchange Program in the future. The unit will start with a reading activity (reading advertisements) to find possible accommodation from the newspaper. Then they will have to ring a few landlords who have rooms or apartments to get further information about the accom-modation advertised (speaking/listening practice) and so on until they get the good accommodation they need at the right cost they can afford. In this way, a story line can be constructed for the whole programs (with various themes and sub-themes) to make the program more interesting.